LABORATORIUM IBADAH BAGI ORANG PERCAYA-ANALISA NARASI 1 SAMUEL 1 - GUMULYA DJUHARTO (SOLA GRATIA: Jurnal Teologi Biblika dan Praktika, 2016)
Abstract: Reading Hannah‘s success to overcome life‘s dilemma proved that the true worship based on the sincerity of heart will be a kind of laboratory and clinic for healing. It is a place where believers had an experience of recovery process and finding solution even though someone can give an unsuitable reaction toward their condition. As long as the attitude of trusting God becomes an integral part of believer‘s life, they can always find hope in God.  Keywords: Laboratory, Worship, Reaction, Finding Solution